The Relationship Between Body Mass Index and Concentration Levels in Nutrition Students: A Transversal Correlation Study - Nurul Afifah, Anisah; Hasmyati, Hasmyati; Kasmad, Rachmad (Journal of Nutrition and Public Health, 2025)
Background: Nutritional status is a crucial factor influencing students' cognitive abilities and comprehension during the learning process. Concentration is a crucial mental aspect for mastering course material, but it is easily disrupted by internal and external factors, including inadequate nutrition, such as skipping breakfast. Initial observations of students in the Nutrition Study Program at the Faculty of Public Health, Universitas Negeri Medan (UNM) revealed a diversity of nutritional statuses and complaints of difficulty focusing (easily feeling sleepy) during lectures if they skip breakfast. Aims:This study aims to analyze and prove the relationship between nutritional status and concentration levels in students of the Nutrition Study Program, Faculty of Sport and Health Sciences, Makassar State University (UNM). Methods: The type of research used is quantitative with a descriptive correlation design using a Cross Sectional approach. The study population was students of the Nutrition Study Program aged 18-22 years, with a total of 66 respondents selected through a purposive sampling technique. Measurement of nutritional status was carried out through anthropometric measurements (weight and height) which were converted into Body Mass Index (BMI). The concentration level was measured using the Test Grid Concentration. Data were analyzed using descriptive tests, normality tests, and Pearson correlation tests with the SPSS 23 program. Result: The results of the descriptive analysis showed that most respondents had Normal nutritional status (41 of 66 respondents) and were in the Good concentration category (33 of 66 respondents)10. The results of the Pearson correlation test between nutritional status and concentration level produced a statistical value of P = 0.78. Conclusion: Based on the statistical analysis, it was concluded that there was no significant relationship between nutritional status and concentration levels of students in the Nutrition Study Program at FIKK UNM (p = 0.078). This result indicates that in the study population, nutritional status was not the primary factor influencing learning concentration, but rather was influenced by other factors such as breakfast habits and physical condition.